Fetal Perocephalus and ascitis in a non descript doe - a case report - REDDY, K C S; RAJU, K G S; RAO, K S (The Indian Journal of Animal Reproduction, 2007)
A case of dystocia due to fetal perocephalus and ascitis in a doe was reported.